2021
DOI: 10.1186/s13023-021-02119-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety and effectiveness of velaglucerase alfa in Gaucher disease: 6-year interim analysis of a post-marketing surveillance in Japan

Abstract: Background Gaucher disease (GD) is caused by reduced lysosomal enzyme β-glucocerebrosidase activity. Heterogeneous genotypes and phenotypes have been observed within GD types and across ethnicities. Enzyme replacement therapy is generally recommended for patients with type 1 GD, the least severe form of GD. In Japan, velaglucerase alfa has a broad indication covering type 1, 2 or 3 GD.  Methods All patients with type 1, 2, or 3 GD administered vela… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Although, some patients improved after the switch, and others deteriorated ( Supplementary Table S2 ), our data confirms that in the majority of the patients, switching from ERT to SRT maintained stability in the key disease parameters. Variable responses were also seen by Kleytman et al [ 12 ], however, in this study, the improvements in spleen volume, platelet count, chitotriosidase, and lyso-Gb1 following the switch seems to be more significant. Since the characteristics of the patients in the two studies are rather similar, we speculate that the differences in the results could be explained by the different nature of the report.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Although, some patients improved after the switch, and others deteriorated ( Supplementary Table S2 ), our data confirms that in the majority of the patients, switching from ERT to SRT maintained stability in the key disease parameters. Variable responses were also seen by Kleytman et al [ 12 ], however, in this study, the improvements in spleen volume, platelet count, chitotriosidase, and lyso-Gb1 following the switch seems to be more significant. Since the characteristics of the patients in the two studies are rather similar, we speculate that the differences in the results could be explained by the different nature of the report.…”
Section: Discussionsupporting
confidence: 58%
“…For example, Deegan and Cox reported in 2012 that only 3 of 262 (1.1%) patients discontinued imiglucerase due to AE [ 11 ]. A study from Japan showed that only one of 53 patients, including all three types of GD, stopped Velaglucerase alfa due to an AE (1.9%) [ 12 ]. These numbers support our basic approach towards eliglustat as a second-line therapy as previously discussed [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, IFN-γ administration did not lead to an inflammatory syndrome with a high temperature or to a recurrence of HLH-like manifestations. The main risk of providing exogenous protein to compensate for the genetic deficiency of the endogenous protein is the development of neutralizing antibodies, which have been observed in a subset of patients with inherited deficiencies of coagulation proteins (e.g., factors VII, VIII, and IX) [ 58 ], ß-glucocerebrosidase factor deficiency underlying Gaucher disease [ 59 ], and adenosine deaminase deficiency underlying severe combined immunodeficiency [ 60 ]. No neutralizing anti-IFN-γ auto-Abs were detected in the serum of the patient during the 30 months of treatment administration.…”
Section: Discussionmentioning
confidence: 99%
“…No case of GD with the p.L483R variant has been reported in Nepal, and it is unclear whether p.L483R is a common variant in Nepalese. ERT has been approved as the first-line treatment for GD2 in Japan [ 31 ]. The first patient's hematological abnormalities and hepatosplenomegaly improved after ERT but her neurological symptoms gradually worsened.…”
Section: Discussionmentioning
confidence: 99%